Highly efficient and eco-friendly green quantum dot light-emitting diodes through interfacial potential grading - Yuhe Bi; Jianhui Sun; Sheng Cao; Qiuyan Li; Jinju Zheng; Xi Yuan; Yunjun Wang; Bingsuo Zou; Jialong Zhao (Nature Communications)
Abstract As next-generation display technologies, eco-friendly colloidal quantum dot light-emitting diodes have drawn great attention due to their excellent luminescence properties, along with their rapid development. However, practical applications of eco-friendly quantum dot light-emitting device remain challenging, primarily due to the inferior performance of green device, which still lag behind their red and blue counterparts. Herein, we present efficient green device based on interfacial potential-graded ZnSeTe quantum dots. Our findings show that this potential-graded structure alleviates interfacial lattice mismatch and strain, reducing structural deformation and misfit defects. The smoothed interfacial potential suppresses the nonradiative recombination processes, particularly Auger recombination revealed by excitation-intensity dependent ultrafast transient absorption kinetics. Consequently, the interfacial potential-graded quantum dots demonstrate highly efficient green quantum dot light-emitting diodes, with a peak external quantum efficiency of 21.7% at 520 nm and a corresponding current efficiency of 75.7 cd A−1.